2013
DOI: 10.1136/bcr-2013-200609
|View full text |Cite
|
Sign up to set email alerts
|

Migration of a fractured ventriculoperitoneal shunt into the scrotum: a rare complication

Abstract: DESCRIPTIONChildren with hydrocephalus are commonly treated with a ventriculoperitoneal (VP) shunt for diversion of CSF. Unfortunately, complications arising from VP shunting are not uncommon. Apart from shunt blockage and infection, it may become disconnected or fractured and migrate into the potential spaces or viscera.Here we present images of a unique complication of VP shunt in a 14-year-old boy who had a background history of congenital hydrocephalus. At the age of 13 years, he had a fracture of the righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 1 publication
1
14
0
1
Order By: Relevance
“…The issue of the length of peritoneal catheter and complications related to it has been discussed in the literature and suggests that use of full-length peritoneal shunt catheter is not associated with an increase in complications and eliminates the need to lengthen the peritoneal catheter for growth of the child [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of the length of peritoneal catheter and complications related to it has been discussed in the literature and suggests that use of full-length peritoneal shunt catheter is not associated with an increase in complications and eliminates the need to lengthen the peritoneal catheter for growth of the child [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…After placement, however, complications are frequent, especially in children. Shunt migration through a patent processus vaginalis within the scrotal sac is a rare event, with only a few cases reported till date [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. We report a case of scrotal migration of VP shunt in a 1-year-old boy, through patent processus vaginalis, who had a background history of congenital hydrocephalus.…”
Section: Introductionmentioning
confidence: 99%
“…However, the migration of VPS tip into the hernial sac is a rare event. Shahizon et al reported a case of scrotal mass formed by coiling of a fractured end of VPS migrating into the scrotum within the hernia sac 8. Lee et al reported a case of VPS migration into the scrotum of an adult male 9.…”
Section: Discussionmentioning
confidence: 99%
“…Shunt migration within the hernia sac is an even rarer event. A fractured end of VP shunt tubing migrating to the scrotum within the hernia sac and coiling to form a scrotal mass has also been reported [2]. Lee et al [3] compiled data on cases where a VP shunt migrated into the inguinal hernia sac.…”
Section: Discussionmentioning
confidence: 99%